A Theoretical Framework on Reflection in Service Learning: Deepening Reflection Through Identity Development - Kawai, Toru (Frontiers in Education, 2021)
In higher education, well-designed service learning combines service activities and academic knowledge in reflection, generating essential learning outcomes: academic enhancement, personal growth, and civic engagement. As research on reflection in service learning has shown, the process of reflection deepens through description of service experiences, examination of those experiences and articulation of learning. This article provides a theoretical explanation of deepening the reflection process by incorporating reflection theory and identity theory of college student development, professional development, and general identity development. Expanding the theoretical explanation of the reflective process clarifies the conditions of the deepening student reflection process in service learning in the following ways. First, it focuses on concrete experience then-and-there at that moment rather than abstract impressions by paying attention to personal dissonance in the experience. In addition, it finds discrepancies from differences of views, perspectives, and backgrounds between those of students and others. It connects outward exploration of those differences and inward exploration to construct internal voices toward self-authorship. The deep reflection process requires confronting contradictions through dialogical interplays among the I-positions of their own and others. It bridges discontinuities between past, present, and future selves by expanding the time perspective retrospectively and prospectively, and solving contradictions embedding in their prejudice. Furthermore, it activates plurality in social norms and values. The above conditions should be design principles for deepening critical and dialogical reflection in high-impact service learning. Through deepening reflection in service learning, it can be expected to activate mutuality and support ethical generativity toward solidarity against hostility.